Association with pregnancy increases the risk of local recurrence but does not impact overall survival in breast cancer: A case–control study of 87 cases. (December 2016) - Genin, A.S.; De Rycke, Y.; Stevens, D.; Donnadieu, A.; Langer, A.; Rouzier, R.; Lerebours, F.
Abstract: Pregnancy-associated breast cancer (PABC) constitutes 7% of all BCs in young women. The prognosis of PABC remains controversial. In this study, we evaluated the impact of the association of pregnancy with BC on the rates of overall survival (OS), disease free survival (DFS), and distant and local recurrence-free survival. We conducted a retrospective unicenter case–control study. We enrolled PABC patients treated at our institution between 1992 and 2009. For each case, 2 BC controls were matched for age and year of diagnosis. Univariate and multivariate analyses were performed to assess the parameters associated with prognosis. Eighty-seven PABC patients were enrolled and matched with 174 controls. The univariate analysis did not reveal any significant differences in OS, DFS or distant recurrence rates between the 2 groups. Pregnancy associated status, a tumor larger than T2 and neoadjuvant chemotherapy as the primary treatment were significantly associated with an increased risk of local relapse. The multivariate analysis showed that the pregnancy associated status and the tumor size were strong prognostic factors of local recurrence. Pregnancy associated status negates the prognostic value of tumor size, as both T0–T2 and T3–T4 PABC patients have the same poor prognosis as control BC patients with T3–T4 tumors. Interestingly, although PABC patients have more locally advanced tumors, they did not have a higher rate of radical surgery than the control BC patients. Pregnancy associated status is a strong prognostic factor of local relapse in BC. In PABC patients, when possible, radical surgery should be the preferred first treatment step.